Junctional epidermolysis bullosa: genotype-phenotype correlations - Alexey A. Kubanov; Vadim V. Chikin; Arfenya E. Karamova; Ekaterina S. Monchakovskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Junctional epidermolysis bullosa most commonly results from mutations in the LAMA3, LAMB3, LAMC2, COL17A1, ITGA6 and ITGB4 genes. Junctional epidermolysis bullosa is characterized by clinical heterogeneity. To date, scientific findings allow to evaluate correlations between the severity of clinical manifestations and genetic defects underlying in the development of the disease. A systematic literature search was performed using PubMed and RSCI, and keywords including junctional epidermolysis bullosa, laminin 332, collagen XVII, 64 integrin. The review includes description of clinical findings of junctional epidermolysis bullosa, mutation location and types, its impact on protein production and functions. To evaluate the impact of gene mutation on protein functions, this review explores the structure and functions of lamina lucida components, including laminin 332, collagen XVII and 64 integrin, which are frequently associated with the development of junctional epidermolysis bullosa. The correlation between severe types of junctional epidermolysis bullosa and mutations resulting in premature stop codon generation and complete absence of protein expression has been described. Although, genotype-phenotype correlations should be analyzed carefully due to mechanisms which enable to improve protein expression.